2011
DOI: 10.1182/blood-2011-03-344051
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic effects of rituximab on the human spleen in immune thrombocytopenia

Abstract: Immune thrombocytopenia (ITP) is an autoimmune disease with a complex pathogenesis. As in many B cell-related autoimmune diseases, rituximab (RTX) has been shown to increase platelet counts in some ITP patients. From an immunologic standpoint, the mode of action of RTX and the reasons underlying its limited efficacy have yet to be elucidated. Because splenectomy is a cornerstone treatment of ITP, the immune effect of RTX on this major secondary lymphoid organ was in-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
97
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(107 citation statements)
references
References 38 publications
8
97
2
Order By: Relevance
“…[29][30][31][32][33] However, several studies have shown that rituximab therapy effectively eliminates B cells from the peripheral blood but fails to effectively deplete all B cells within secondary lymphoid tissues. [34][35][36][37][38][39] Thus, whether PCs remaining in this setting are long-lived or dependent on replenishment by the residual B cells is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31][32][33] However, several studies have shown that rituximab therapy effectively eliminates B cells from the peripheral blood but fails to effectively deplete all B cells within secondary lymphoid tissues. [34][35][36][37][38][39] Thus, whether PCs remaining in this setting are long-lived or dependent on replenishment by the residual B cells is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…41 However, Audia et al reported different results that RTX showed no effect on Tregs in ITP. 43 More clinical trials with large sample sizes are required to further investigate the sustained response of the combination of RTX and rhTPO.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous studies have indicated that regulatory T cells (Treg) are deficient, both in the blood and the spleen of ITP patients. 12,13 More recently, a decrease in circulating CD19 1 CD24 hi CD38 hi B cells and in the overall production of interleukin 10 (IL-10) by B cells has also been reported, consistent with a regulatory B-cell deficiency.…”
Section: Introductionmentioning
confidence: 88%
“…12 On the other hand, we have shown that failure to respond to RTX was associated with the persistence of splenic plasma cells producing anti-platelet antibodies 29 and to an imbalance between effector and regulatory T cells in the spleens of ITP patients who do not respond to RTX, consistent with an increase in the Th1/Treg ratio. 13 We thus hypothesized that such an imbalance may foster CD8…”
Section: Introductionmentioning
confidence: 99%